2021
DOI: 10.1002/dc.24868
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic olfactory neuroblastoma: A small round blue cell puzzle on fine‐needle aspiration cytology

Abstract: Small round blue cell tumors (SRBCTs) are a heterogeneous group of malignant neoplasms that can be challenging to distinguish on fine-needle aspiration (FNA) cytology. Ancillary tests as well as clinico-radiological correlation are often required to make an accurate diagnosis. FNA is a low-cost, low-infrastructure test, making it a coveted diagnostic tool, especially in low-resource settings. Olfactory neuroblastoma (ONB) is a rare SRBCT encountered in both pediatric and adult patients. Awareness of the cytomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…4,5 However, these are merely suggestive, but not pathognomonic of a diagnosis of ONB, since they are also seen in other neuroendocrine and other small round cell tumors. 4,5 Mahooti et al found that identification of background neuropil along with rosettes is critical in rendering a diagnosis of ONB on aspirates. 12 However, the caveat is that this finding, although specific, is not unequivocally present in all ONB aspirates, as also seen in our study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 However, these are merely suggestive, but not pathognomonic of a diagnosis of ONB, since they are also seen in other neuroendocrine and other small round cell tumors. 4,5 Mahooti et al found that identification of background neuropil along with rosettes is critical in rendering a diagnosis of ONB on aspirates. 12 However, the caveat is that this finding, although specific, is not unequivocally present in all ONB aspirates, as also seen in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The cytomorphological features of ONB described in literature include high cellularity, distribution as cellular clusters and single cells, presence of nuclear moulding, paranuclear blue bodies and necrosis, and the absence of lymphoglandular bodies, amongst others 4,5 . However, these are merely suggestive, but not pathognomonic of a diagnosis of ONB, since they are also seen in other neuroendocrine and other small round cell tumors 4,5 . Mahooti et al found that identification of background neuropil along with rosettes is critical in rendering a diagnosis of ONB on aspirates 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 In another smaller case series, Penzhorn and Schubert describe the use of FNA in the evaluation of metastatic olfactory neuroblastoma and its cytologic differential diagnosis with other small round blue cell tumors, which can be addressed if adequate cell block material is available. 18 Despite the rarity of sinonasal cancers, most patients with metastatic disease detected by FNA have a known primary, which, in combination with limited ancillary studies, facilitates the cytologic interpretation of these challenging cases. 18 A major hurdle in the development of improved treatments for patients with sinonasal malignancies is that these tumors are rare, and funding for the study of such cancers is very limited.…”
mentioning
confidence: 99%